2019
DOI: 10.1093/jxb/erz430
|View full text |Cite
|
Sign up to set email alerts
|

ABF2 and MYB transcription factors regulate feruloyl transferase FHT involved in ABA-mediated wound suberization of kiwifruit

Abstract: Activation of the kiwifruit suberin biosynthesis gene AchnFHT is coordinately controlled via repression by AchnMYB4 and promotion by AchnABF2, AchnMYB41, and AchnMYB107.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 47 publications
0
36
0
1
Order By: Relevance
“…GmSRS18, as a transcription factor, was located in the cell nucleus, which showed that it functions in cell nucleus. Transcription factors were involved in the abiotic and biotic stress response in many plants [67][68][69][70][71][72]. Though there are few reports of SRS family about the abiotic stress response thus far, we demonstrated that GmSRS18 can increase the transgenic Arabidopsis sensitivity to drought and salt stresses.…”
Section: Discussionmentioning
confidence: 70%
“…GmSRS18, as a transcription factor, was located in the cell nucleus, which showed that it functions in cell nucleus. Transcription factors were involved in the abiotic and biotic stress response in many plants [67][68][69][70][71][72]. Though there are few reports of SRS family about the abiotic stress response thus far, we demonstrated that GmSRS18 can increase the transgenic Arabidopsis sensitivity to drought and salt stresses.…”
Section: Discussionmentioning
confidence: 70%
“…To speak to this, a number of TFs that function as positive regulators of polyaliphatic suberin biosynthesis have been identified. These include Arabidopsis AtMYB107 (Gou et al ., 2017), AtMYB9 (Lashbrooke et al ., 2016), AtMYB36 (Wang et al ., 2020), AtMYB39 (Cohen et al ., 2020; Wang et al ., 2020), AtMYB41 (Kosma et al ., 2014), AtMYB92 (To et al, 2020) , AtNAC046 (Mahmood et al ., 2019), AtNAC058 (Markus, 2018), apple ( Malus domestica ) MdMYB93 (Legay et al ., 2016), and kiwi ( Actinidia deliciosa ) AchnMYB41, AchnMYB107, AchnMYC2, and AchnABF2 (Han et al ., 2017; Wei et al ., 2020). Kiwi AchnMYB4 (Wei et al ., 2020) was identified as a negative transcriptional regulator of a kiwi ortholog of FHT .…”
Section: Discussionmentioning
confidence: 99%
“…Before this study, two other TFs had been implicated in regulating suberin; however, definitive biochemical evidence was not presented (Almeida et al ., 2013; Lasserre et al ., 2008). Since then, a number of TFs that regulate tissue‐ and condition‐specific suberin deposition have been discovered (Cohen et al ., 2020; Gou et al ., 2017; Lashbrooke et al ., 2016; Legay et al ., 2016; Verdaguer et al ., 2016; Wei et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies are showing the importance of distinct clades of the MYB transcription factor family as conserved regulators of suberin deposition in response to osmotic stress in different cell types and in phylogenetically distant plants, linking their evolution with colonization of dry terrestrial environments by early land plants (Capote et al, 2018;Cohen, Fedyuk, Wang, Wu, & Aharoni, 2020;Gou et al, 2017;Kajala et al, 2021;Kosma et al, 2014;Lashbrooke et al, 2016;Legay et al, 2016;Shukla et al, 2021;To et al, 2020;Wei et al, 2020). Two of the possible scenarios are: (1) osmotic stress-inducible regulation of suberization diversified from pre-existing developmental pathways, (2) the regulation of suberization in response to drought was re-activated as plants colonized drier environments.…”
Section: Root Cell Type Grn Adaptations To Drought: Impermeabilization Of Endodermis and Exodermismentioning
confidence: 99%